A Study on Geotechnical Properties of Weak Rocks in Sudan (Journal of Building and Road Research, 2021)
Weak rocks are available in different areas in Sudan. These include sandstone, mudstone, siltstone usually referred to as Nubian Formations (N.F.). Clastic limestones are present in other areas of Sudan. Organic limestones in the form of coralline deposits are present in eastern Sudan, mainly on the Red Sea coast. Weak rocks constitute an important geological feature on which the foundations of most of the important structures are resting. The sandstone is also used as a primary buildingmaterial or as a facing stone over other construction. The geotechnical properties of these formations were investigated bydifferent insitu and laboratory testing methods. This paper summarizes the origin, distribution of Nubian formation and limestone. The paper also presents most of available data on the geotechnical properties of these formations. It is concluded that the Nubian formation and limestone coral deposit are weak rocks with poor quality of core samples; hence feld testingmay give better geocharacterization result for such deposit.
Keywords: Geotechnical Properties; Weak Rocks